دور التشبيك في تحقيق الميزة التنافسية للمشروعات الفندقية دراسة ميدانية على الفنادق العاملة في مدينة اللاذقية - زاهر بسام; لايقة هشام (Latakia University Journal - Economic and Legal Sciences Series, 2018)
هدفت هذه الدراسة إلى التعرف على مدى وجود تشبيك وتعاون فيما بين الفنادق، وطبيعته ونوعه وديمومته ودوره في تحقيق الميزة التنافسية للمشروعات السياحية الفندقية العاملة في مدينة اللاذقية. ولتحقيق أهداف الدراسة فقد طوّر الباحث استبانه لجمع البيانات، شمل مجتمع البحث جميع مدراء الفنادق في اللاذقية في (69) فندقاً، وقد اختار الباحث عينة ميسرة من موظفي الإدارة العليا لـ (18) فندقاً وقد تم توزيع ثلاثة استبيانات لكل فندق ليصبح عدد الاستبيانات الموزعة (54) استبياناً، وهي من فنادق (5-4-3) نجوم فقط نظراً لنضوج تلك الفنادق في العمل السياحي الفندقي وإمكانية الاستفادة من الخبرة التي يمتلكونها في السوق وخاصة في مجال العلاقات الاجتماعية. خلصت الدراسة إلى نتائج أهمها أنه لا يوجد تشبيك بين الفنادق محل البحث في مرحلة البدء والانطلاق, و أنّ مديري تلك الفنادق يوافقون بدرجة متوسطة على تعاون الفندق مع الجامعات لابتكار خدمات جديدة. كما تسعى الفنادق للبحث عن شركاء في نفس المجال، أن التشبيك يؤثر على نجاح الفندق، وأن الفندق يعمل على تبادل المعلومات مع المنشآت الأخرى السياحية، وأن التشبيك يساعد على إنتاج خدمات مكملة للمشروع السياحي. وجود فروق ذات دلالة إحصائية بين متوسط إجابات أفراد العينة حول أهميّة التشبيك، وأن مدراء الفنادق محل البحث يوافقون على أهميّة التشبيك. وأخيراً وجود فروق ذات دلالة إحصائية بين متوسط إجابات أفراد العينة الخاص بدور التشبيك في تعزيز الميزة التنافسية وبالتالي فإن التشبيك يسهم في تعزيز الميزة التنافسية للمشروعات السياحية الفندقية. This study aimed to identify the extent of the existence of networking and cooperation among hotels and nature, type, and its lifetime and its role in achieving competitive advantage of the tourist hotel projects operating in the city of Lattakia. To achieve the objectives of the study were researcher developed a questionnaire to collect data, including the research community all hotel managers in Lattakia in 69 hotels, the researcher has chosen soft sample of senior management personnel for 18 hotels have been three questionnaires each hotel distribution bringing the total number of distributed questionnaires ( 54) questionnaire, one of the hotels (5-4-3) stars only due to the maturation of those hotels in the tourist hotel work and the possibility of benefiting from the expertise they hold in the market, especially in the field of social relations. The study concluded the following results; that no networking between the hotels in the beginning and start-up phase, and that the managers of those hotels agree moderately on the hotel’s cooperation with universities to create new services. It also seeks hotels to search for partners in the same field, the networking affect the success of the hotel, and the hotel is working on the exchange of information with other tourist enterprises, and that networking helps produce complementary services to the tourism project. And no statistically significant between the average Answers private respondents of the importance of networking differences, and hotel managers agree on the importance of networking. Finally, no statistically significant differences between the average answers of respondents about the networking role in enhancing the competitive advantage and therefore the networking contributes to promoting the competitiveness of the tourist hotel projects.